Special Issue “Delivery Systems of Peptides and Proteins: Challenges, Status Quo and Future Perspectives” - Wenjuan Liu; Haisheng He; Jianping Qi (Pharmaceuticals, 2023)
Peptides and proteins have emerged as more important therapeutic molecules compared to small molecular chemicals due to their high specificity and efficacy and low toxicity [...]